Money does not stink: Using unpleasant odors as stimulus material changes risky decision making - Bettina von Helversen; Géraldine Coppin; Benjamin Scheibehenne (Journal of Behavioral Decision Making, 2020)
Odors are strong elicitors of affect, and they play an important role in guiding human behavior, such as avoiding fire or spoiled food. However, little is known about how risky decision making changes when stimuli are olfactory. We investigated this question in an experimental study of risky decision making with unpleasant odors and monetary losses in a fully incentivized task with real outcomes. Odor and monetary decisions were matched so that monetary losses corresponded to the amount of money participants were willing to pay to avoid smelling an odor. Hierarchical Bayesian analyses using prospect theory show that participants were less sensitive to probabilities when gambling with odors than when gambling with money. These results highlight the importance of taking the sensory modality into account when studying risky decision making.
Keywords: 650; affect; odors; probability weighting; prospect theory; risky decision making